GAMBARAN FUNGSI KOGNITIF PADA LANSIA MENGGUNAKAN MINI-MENTAL STATE EXAMINATION (MMSE) DI KELURAHAN KAUMAN KIDUL SALATIGA - Restu Septian Ayu Vita Efendi; Puji Purwaningsih (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
One of the natural processes in the development phase of the elderly is mental disorders. Mental disorders in the form of decreased cognitive function include perception, thinking, disorientation towards time and place and difficulty accepting new ideas. The nurse's role in this case is to carry out health screening to detect early mental health in the elderly. The aim of this research is to determine the results of the analysis of the cognitive function of the elderly using the Mini-Mental State Examination (MMSE) in Kauman Kidul Village, Salatiga City. This research design uses a descriptive method with a descriptive analytical approach. Sampling using proportional random sampling obtained a sample of 203 respondents. Data collection used the Mini-Mental State Examination (MMSE) instrument with a validity value of r: 0.776 and reliability r: 0.827. The research results showed that there were 124 elderly respondents with normal cognitive function, 74 respondents with mild cognitive impairment, and 5 respondents with moderate cognitive impairment. The results of the research showed that the number of elderly with normal cognitive function was greater than the elderly who experienced decreased cognitive function, this was because the elderly in this study were dominated by young elderly. However, elderly people who experience cognitive decline cannot be avoided because it could be due to physiological changes in brain structure that occur normally as they age. Â The elderly are expected to change and maintain an active lifestyle and participate in certain activities throughout their lives to prevent a decline in cognitive function and families are expected to provide emotional support in the form of special attention to the elderly to prevent impairment of their cognitive function.